If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(-8 + 3x) = -4x + -31 (-8 * 7 + 3x * 7) = -4x + -31 (-56 + 21x) = -4x + -31 Reorder the terms: -56 + 21x = -31 + -4x Solving -56 + 21x = -31 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -56 + 21x + 4x = -31 + -4x + 4x Combine like terms: 21x + 4x = 25x -56 + 25x = -31 + -4x + 4x Combine like terms: -4x + 4x = 0 -56 + 25x = -31 + 0 -56 + 25x = -31 Add '56' to each side of the equation. -56 + 56 + 25x = -31 + 56 Combine like terms: -56 + 56 = 0 0 + 25x = -31 + 56 25x = -31 + 56 Combine like terms: -31 + 56 = 25 25x = 25 Divide each side by '25'. x = 1 Simplifying x = 1
| 4(n-8)=-12 | | n+4=-16+6n | | n-1=9-n | | 7(-n-3)-7(1+2n)=-7 | | 15p^2-14p+3=0 | | -4(x+2)-(x-4)=6 | | -5x-15=-7x+5 | | 107=2(-6-7n)+7 | | V=nr/2/h | | 3-2x+1=12 | | 3-(6x-54)=3 | | -4b-6b=20 | | 7x+98=-5+2 | | 3v^2-47v-16=0 | | P+0.04p=22.88 | | -8c+1=2 | | 3y+4y=32 | | s^2-16s=0 | | (x-1)(x+2)(x+3)(x+6)-160=0 | | 2-0.3(x+1)=4.4-0.6x | | .4(x-.5)=.25(x+8) | | v^2-23v=0 | | 1-5m=5 | | -1/2x-2=1 | | 1-5m=9 | | K^2-24k= | | 0.5y+2=0.75+12 | | u^2-13u=0 | | 9a+6b-(7a-4b)+2= | | -30x+60=4-16x | | -(3r+5)=4r-1 | | Y-3y=2-4y |